Four-armed Kubera accompanied by his elephant - Temples of India Project Team (Jio Institute, 2024)
Kubera, accompanied by his elephant vehicle, is depicted with four arms on the kakshasana (seat back) wall of the Undeshwar Temple. He holds a money bag in his upper arms. Although his lower arms are damaged, it appears that he was originally holding a mace and a water pot in his lower right and left hand, respectively.